NGAYAH: TRANSFORMASI NILAI SOSIAL - Ni Nyoman Wati (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2008)
This paper describes a performance entitled ngayah, that is an important activities in Balinese society.  The activities which do not aimed to gain material advantages is  assumed  consist of high value in society.   Based on experience through her whole life  and research held on three cases, the writer transformed those social activities to the  performing art.   The performance means to aware and actualize the value of ngayah in  contemporary era. Key words: ngayah, social activities, value, performance.